Artificial Intelligence in Istinbat Al-Hukm from Muamalah Hadiths: a Fiqh and Library-Based Analysis - Muhmmad Irkham Firdaus; Muhammad Abdul Aziz; M. Abdurrozaq (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2026)
The complexity of Hadith verification and the current diversity of schools of thought (madhhab) necessitate Artificial Intelligence (AI)-based solutions to provide a more efficient, structured, and unbiased analysis. The integration of AI raises fundamental questions regarding the normative authority of its legal outcomes, specifically whether AI can replace the role of a Mujtahid, who possesses intellect (aql) and intention (niyyah). Therefore, this study aims to analyze the shar'i ruling on the use of AI from a Fiqh perspective, focusing on three areas: mapping the technical capabilities of AI in Hadith and Usul Fiqh analysis, assessing the shar'i legal validity of AI products as either a hukm (binding ruling) or a wasīlah (aid/tool), and formulating an Islamic ethical framework (Akhlaq) for its development. This study employs a qualitative research method with a library research approach, comprehensively analyzing and interpreting data from primary and secondary literature, academic journals, and publications from fatwa institutions related to Usul Fiqh, technological ethics, and the implementation of AI in the religious field. Data analysis is conducted using a descriptive-analytical technique, where data concerning AI capabilities and Usul Fiqh principles are collected, classified, and critically analyzed to produce a systematic legal synthesis and ethical framework. The results of this study explain that the utilization of Artificial Intelligence (AI) in Istinbāṭ al-Hukm is fundamentally permissible (mubah) as it supports the principles of Taisīr (ease) and Maslahah (public interest), making it an effective aid (wasīlah) for technical tasks such as sanad verification, data classification, and the analysis of Qat'i al-Dilālah Hadiths. However, the outcomes of istinbāṭ ḥukm generated by AI cannot be accepted as shar'i-ly binding legal decisions. This is because the authority of Ijtihād is inherently attached to humans, which is essential for understanding the Maqāṣid al-Sharī‘ah. Consequently, AI output must be treated as logical predictions that must be validated by a human Mujtahid. Furthermore, the use of AI is prohibited for Muamalah Hadiths, as the proofs (dalil) in muamalah fall under the category of Ẓannī al-Dilālah (speculative in meaning), which lack a single, clear, or direct definitive meaning, thus requiring further analysis, interpretation, or explanation to understand their true intended meaning.